2019
DOI: 10.1021/acschembio.9b00063
|View full text |Cite
|
Sign up to set email alerts
|

Toolbox of Diverse Linkers for Navigating the Cellular Efficacy Landscape of Stapled Peptides

Abstract: Stapled peptides have great potential as modulators of protein–protein interactions (PPIs). However, there is a vast landscape of chemical features that can be varied for any given peptide, and identifying a set of features that maximizes cellular uptake and subsequent target engagement remains a key challenge. Herein, we present a systematic analysis of staple functionality on the peptide bioactivity landscape in cellular assays. Through application of a “toolbox” of diversified dialkynyl linkers to the stapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 57 publications
(86 reference statements)
0
27
0
Order By: Relevance
“…In an example where peptide-small molecule hybrids were investigated in a biological context, Spring and co-workers found a small molecule carrier (SMoC) group incorporated through the cyclising linker can enhance the cellular uptake of a series MDM2binding peptides. 118 SMoCs are molecules that possess guanidinium cations linked to a lipophilic biphenyl system; they were designed by Selwood and co-workers to be a smaller and potentially more proteolytically stable mimic of guanidine-rich cell-penetrating peptides. 119 Higher uptake for the SMoC-bearing MDM2-binding peptide was visualised by confocal microscopy, which correlated with an improvement in p53 activation in cells.…”
Section: Cell Permeabilitymentioning
confidence: 99%
“…In an example where peptide-small molecule hybrids were investigated in a biological context, Spring and co-workers found a small molecule carrier (SMoC) group incorporated through the cyclising linker can enhance the cellular uptake of a series MDM2binding peptides. 118 SMoCs are molecules that possess guanidinium cations linked to a lipophilic biphenyl system; they were designed by Selwood and co-workers to be a smaller and potentially more proteolytically stable mimic of guanidine-rich cell-penetrating peptides. 119 Higher uptake for the SMoC-bearing MDM2-binding peptide was visualised by confocal microscopy, which correlated with an improvement in p53 activation in cells.…”
Section: Cell Permeabilitymentioning
confidence: 99%
“…[ 142 ] Only a few studies have directly compared the effects of different types of staple chemistry on similar sequences, therefore it is difficult to generalise about the impact of staples on factors such as helicity, or cell uptake. [ 31 ] Maximising helicity has been one of the principle aims of many chemical studies, but it has been shown that flexibility in macrocyclic structures is often critical in allowing a peptide to cross the cellular lipid membrane. [ 145 ]…”
Section: Section 2: Selection and Placement Of The Staple Residuesmentioning
confidence: 99%
“…Functionalisation is not limited to fluorescence, and Wu et al ., describe a library of functionalised dialkynyl linkers compatible with double CuAAC stapling of peptides (Figure 9B); these include linkers with additional non‐peptidic polyamines and nuclear targeting peptides. [ 31 ] It was shown that in vitro binding affinity for MDM2 was not significantly affected by the linker chemistry; but positively charged residues enhanced both cellular uptake and target engagement in cell reporter assays.…”
Section: Section 3: Adding Functionality To the Stapled Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, most peptide stapling strategies are limited to helical motifs. Because LIR motifs bind LC3B in an extended conformation, we applied an innovative diversity‐oriented stapling strategy that does not assume any specific secondary structure …”
Section: Introductionmentioning
confidence: 99%